Corporate Social Responsibility (CSR) Sebagai Instrumen Pendanaan Pembangunan Daerah: Studi Implementasi Sabang Merah Award di Kabupaten Sanggau - Firdaus Firdaus; Parlindungan Hutapea (Journal of Administration, Governance, and Political Issues, 2025)
This study aims to analyse the role of the Sabang Merah Award Programme in Sanggau Regency in optimising the contribution of Corporate Social Responsibility (CSR) to regional development, particularly in increasing company participation, directing CSR fund allocation, and creating synergy between the private sector and the government. The method used is a literature review with a descriptive-qualitative approach, collecting and analysing data from government reports, scientific journals, and related articles. The research findings indicate that this award has successfully increased corporate engagement and the amount of CSR funding support. This success is driven by the implementation of a transparent evaluation mechanism aligned with regional development priorities. However, the study also identified challenges that need to be addressed, including programme sustainability, strengthening CSR assessment indicators, and the need for long-term impact evaluation. Overall, the Sabang Merah Award has proven to be an effective policy instrument and an innovative model with the potential to be adopted by other regions to maximise CSR contributions towards sustainable development.